Analisis faktor yang mempengaruhi perusahaan Di indonesia untuk melakukan pergantian kantor akuntan publik (studi empiris pada perusahaan manufaktur yang terdaftar di bei tahun 2009-2014) - Jati, Pandu Saputra, Drs. Eko Sugiyanto, M.Si (2016)
The study aimed to find the effect of management changes, accountant opinion, client size, public accountant firm's size to auditor switching. Population of the research are manufacturing companies which are listed in "Bursa Efek Indonesia" (BEI) in the year 2009-2014. Sample collecting method which used in this research is method purposive sampling and obtained 35 companies as research sample. The type of the data used is a published audited yearly financial statement. Hypothesis in this research are tested by logistics regression analytical method. Result of this research is that audit opinion and public accountant firm's size have significant effect on auditor switching in Indonesia. While other variables in this research like management changes and client size, do not have significant effect to auditor switching in Indonesia.